2022
DOI: 10.22541/au.165026177.74522827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological interventions for improving the postoperative pain intensity in adults after opioid-based anesthesia: a systematic review and network meta-analysis

Abstract: Background: Opioid-induced hyperalgesia (OIH) is an adverse event after exposure to opioids which would increase pain intensity. The optimal drug to prevent these adverse effects is still unclear. We aimed to perform a network meta-analysis to compare different pharmacological interventions in preventing the increase in postoperative pain caused by OIH. Methods: Several databases were searched independently for randomized-controlled trials (RCTs) comparing different pharmacological interventions in preventing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that use of high-dose remifentanil and fentanyl can result in hyperalgesia [16,20]. However, recent studies have demonstrated that dexmedetomidine infusion can reduce opioid-induced hyperalgesia [21,22]. Third, the timing of PT measurement differs among studies.…”
Section: Trajectory Of Pt and Factors Contributing To Ptvmentioning
confidence: 99%
“…Previous studies have shown that use of high-dose remifentanil and fentanyl can result in hyperalgesia [16,20]. However, recent studies have demonstrated that dexmedetomidine infusion can reduce opioid-induced hyperalgesia [21,22]. Third, the timing of PT measurement differs among studies.…”
Section: Trajectory Of Pt and Factors Contributing To Ptvmentioning
confidence: 99%
“…In the authors' view, it is advisable to critically examine the individual constellation before and during opioid therapy. Furthermore, it is known that the long-term use of opioids can significantly contribute to central sensitization [5,44], which is a relevant factor in EDS patients anyway [11]. Indeed, approaches with opioid-free anesthesia in patients in general [45], but also in hypermobile patients, resulted in reduced postoperative pain levels [46].…”
Section: Pharmacological Pain Treatmentmentioning
confidence: 99%
“…It appears to be a consensus that lower opioid doses and gradual dose tapering will decrease the incidence and severity of OIH [42,44]. Nonopioid analgesic adjuncts and dexmedetomidine also appear to have some utility in the prevention of OIH [45 ▪▪ ] as do magnesium infusions and co-administration with propofol (rather than inhalation anesthetics) [41].…”
Section: Prevention and Treatment Strategiesmentioning
confidence: 99%